An overview of the methods and technical considerations in the valuation of agricultural lands - Cabrido, Candido A. (1990)
The need for accurate valuation of agricultural land in the implementation of land reform cannot be overemphasized. in land valuation, three common methods are used: market approach, income capitalization method and productivity method. The Philippine land reform program has used two methods, one being the productivity approach which during the Marcos Administration was used on rice and corn lands. For all other crops, the present Aquino administration uses a method which combines market value, assessor's market value and landowner's declared value.